Participatory Communication and the Empowerment of the Underdeveloped Communities: A Case of Suku Anak Dalam in Jambi, Indonesia - Ningtias, Rini (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2022)
The Kubu tribe, also known as Suku Anak Dalam (SAD), is an ethnic group that inhabits the Jambi province, Indonesia. They still hold tightly their ancestral culture in their daily life, depend on natural or forest resources, and live a nomadic life. Factors that influence the nomadic life of the SAD community include a belief in â€œMelangunâ€ tradition. The uncontrolled logging and forest fires in Jambi resulted in their loss of forest products to sell to support their life so that their sustainability is in danger. Therefore, there is an urgent need for the empowerment of the SAD community so that they can leave the old culture and live like a modern society. Using a descriptive qualitative method, this research collects the required data by employing interview, observation and documentation techniques. Data analysis uses data reduction techniques, data presentation, and verification. Then the validation technique uses source triangulation by examining data from several sources. The results of the study indicate that to empower Suku Anak Dalam (SAD), it is urgent to use two communication approaches, namely participatory communication and empowerment communication.